2017
DOI: 10.1038/s41598-017-17236-x
|View full text |Cite
|
Sign up to set email alerts
|

Rainbow trout exposed to benzo[a]pyrene yields conserved microRNA binding sites in DNA methyltransferases across 500 million years of evolution

Abstract: The objective of this study was to examine the regulation of DNA methylation following acute (24 h) and prolonged (14 d) exposure to low (1 ng/L) and high (10 ng/L) benzo[a]pyrene. However, with the recent release of the rainbow trout genome, we were able to conduct a more detailed analysis regarding the regulation of the enzymes involved in DNA methylation; DNA methyltransferases (DNMTs). Bioinformatic approaches were used to identify candidate microRNA (miRNA) that potentially bind to the DNMT1 and DNMT3a 3′… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 61 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…Evidence regarding the effect of PAH exposure on Casp8 methylation has not yet been retrieved. For global DNA methylation, the association between PAH exposure and decreased DNA methylation has been reported both in human and animal studies [19, 30, 31]. PAH metabolites in maternal urine are associated with decreased global methylation status in a Chinese cohort [32].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence regarding the effect of PAH exposure on Casp8 methylation has not yet been retrieved. For global DNA methylation, the association between PAH exposure and decreased DNA methylation has been reported both in human and animal studies [19, 30, 31]. PAH metabolites in maternal urine are associated with decreased global methylation status in a Chinese cohort [32].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for crosstalk between DNA level epigenetic modifications and microRNAs remains correlational, as seen in studies using zebrafish and rainbow trout. For example, a strong occupancy of pri-miRNA promtors by H3K4me3 has been observed in zebrafish embryogenesis (Nepal, 2016), while in rainbow trout, a recent gene expression study coupled with in silico predictions suggested an evolutionary deeply conserved crosstalk between miRNA-29 and a dnmt1 paralogue (Kuc et al, 2017). Together, these studies ACCEPTED MANUSCRIPT…”
Section: A C C E P T E D Mmentioning
confidence: 91%
“…conducted in the zebrafish model, testifying to this emerging model's promise to further our understanding of the effects of contaminant exposure on mechanisms regulating DNA methylation dynamics (Kamstra et al, 2015a;Bouwmeester et al, 2016). As such, changes in zebrafish DNA methylation indices have been reported in response to a wide-range of aquatic contaminants, including metals (Gombeau et al, 2016, Zheng et al, 2017Sanchez et al, 2017;Carvan et al, 2017), industrial products (Laing et al, 2016;Santangeli et al, 2016;, pesticides (Wirbisky-Hershberger et al 2017, Qian et al 2017, persistent organic pollutants (POPs; Aluru et al 2014), and polycyclic aromatic hydrocarbons (PAHs;Gao et al 2017;Kuc et al, 2017). With regard to metals, adult zebrafish exposed to 20 g/L depleted uranium exhibited both sex-and tissue-specific changes in global DNA methylation between 7-24 days (Gombeau et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Methods were in alignment with previously published techniques by Kuc et al (2017). An alignment of the collagen transcript (type 1 alpha 1 in most species and type 1 alpha 3 in rainbow trout) was generated to understand the evolutionary conservation of miR-29b binding sites.…”
Section: Bioinformatics Analysismentioning
confidence: 99%